(untitled) (Community Based Medical Journal, 2025)
Retroperitoneal neurofibromas are rare tumors, with an incidence of 3-5% for all neurofibromas. The Schwann cells in the peripheral nerve give rise to these histologically benign tumors. They can be hard to diagnose and treat because of where they are located and their potential to invade the surrounding area and press on nerve roots or other structures. Herein, we report a 17-year-old male patient, who had a complaint of low back pain and pain radiating to the legs, especially on the right side, for one year. MRI and CT scans showed a fairly big (9.7 cm × 4.3 cm) retroperitoneal mass on the right side of the aorta. He also had associated lumbar scoliosis and first lumbar vertebral subluxation. Subsequently, CT-guided core biopsy of the mass provided pathological confirmation indicative of a spindle cell neoplasm consistent with neurofibroma. Retroperitoneal neurofibromas are characterized by their slow growth, and therefore the tumor may not present clinically for a very long time and may only present when it has grown to a considerable size and is exerting pressure on structures in the retroperitoneum. Here, the macroscopic characteristic of a giant size and retroperitoneal location of the tumor gave rise to the low back pain and the radicular leg pain, as it resulted in the compression of spinal nerves. MRI and CT scans were useful in the staging of the tumor prior to surgery, and histologic examination of the biopsy specimen confirmed the diagnosis. This case should serve as a reminder that any rare retroperitoneal neurofibromas, especially those that do not fit traditional clinical presentations, should be approached in a more general and extensive collaboration with clinicians, radiologists, and pathologists. As such, the acute phase must be identified early and treated adequately to avoid other complications and improve the outcomes of the treatment. CBMJ 2025 January: Vol. 14 No. 01 P: 177-181